HUBUNGAN ANTARA BEBAN KERJA MENTAL DENGAN STRES KERJA PADA PERAWAT DI INSTALASI RAWAT INAP RS. TK. II MOH. RIDWAN MEURAKSA JAKARTA TAHUN 2023 - Zakky Shaifuddin Ibrahim (2023)
The extraordinary workload, especially in East Jakarta, often causes work stress for nurses. The purpose of this study was to determine the relationship between mental workload and work stress among nurses working in the outpatient installation at TK II Moh. Ridwan Meuraksa Jakarta. The respondents to this study were nurses who worked in hospitals. This study used a cross-sectional survey with a pre-designed questionnaire. The questionnaire is used to record the mental workload and stress levels of nursing staff at work. Chi-square is used to verify the collected data. With a value of p = 0.034 and OR = 0.353, the results showed that in the inpatient installation room of TK II Moh Ridwan Meuraksa Hospital, Jakarta, there is a significant relationship between the mental workload of nurses and work stress. These results indicate that a high mental workload can increase stress related to the work of nurses. This study has significant implications for dealing with workload and work stress. Hospital management can use research results to develop and implement strategies aimed at reducing the psychological burden and stress associated with the work of nurses